Ethical Dimensions of the Number of Embryos to be Transferred in In Vitro Fertilization - Chervenak, Frank A. (Kluwer Academic Publishers-Plenum Publishers, 2001)
Purpose: We propose an ethically justified policy for the number of embryos to transfer in an in vitro fertilization (IVF), by considering four factors: medical outcomes, patient's preferences, costs, and market forces of providers. Methods: We develop an ethical framework that incorporates three ethical principles: beneficence, respect for autonomy, and justice; and three professional virtues: integrity, compassion, and self-sacrifice. Results: This ethical framework calls for an informed consent process for IVF that provides: information about medical outcomes; information about the risks of multiple gestation; the opportunity to weigh the goal of pregnancy and live birth against the medical and moral risks of multiple gestation; evidence-based recommendations; protection of the woman from potentially coercive influences; and discussion of living with infertility and going to better centers. Conclusion: The number of embryos to be transferred in IVF should mainly be a function of the pregnant women's informed decision. Limiting the number of transferred embryos to two in all cases is not ethically justified at this time.